2019
DOI: 10.3389/fncel.2019.00030
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Improves Brain-Gut Axis by Regulation of 5-HT-Dependent Signaling in the Rat Model of Irritable Bowel Syndrome

Abstract: Irritable bowel syndrome (IBS) is at high risk of co-morbid depression and anxiety, which reduces patients’ quality of life and increases the burden of health care costs. However, the pathophysiological mechanisms responsible for IBS still remain unknown. This study investigated the effects of resveratrol on stress-related depression, anxiety, intestinal and visceral dysfunction in rat model of IBS. Rats received chronic acute combining stress (CACS) for 22 days exhibited depression/anxiety-like behavior, visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 31 publications
2
53
0
2
Order By: Relevance
“…Clinical studies have confirmed that the contents of 5-HT in the intestinal mucosa of patients with GI dysfunction are significantly increased. Other studies have found that EA can regulate the secretion of SP, SP receptor and VIP in the IBS model colon [26] . CRF can induce repeated defecation in rats.…”
Section: Discussionmentioning
confidence: 87%
“…Clinical studies have confirmed that the contents of 5-HT in the intestinal mucosa of patients with GI dysfunction are significantly increased. Other studies have found that EA can regulate the secretion of SP, SP receptor and VIP in the IBS model colon [26] . CRF can induce repeated defecation in rats.…”
Section: Discussionmentioning
confidence: 87%
“…Clinical studies have confirmed that the contents of 5-HT in the intestinal mucosa of patients with GI dysfunction are significantly increased. Other studies have found that electroacupuncture can regulate the secretion of SP, SP receptor and VIP in the IBS model colon [33] . CRF can induce repeated defecation in rats.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies suggested that structural and functional disruptions in BGA cause changes in perceptual and re exive responses of the nervous system and may lead to IBS-D. 5-HT is widely present in the central nervous and gastrointestinal systems in which it plays an important role in the GBA [9]. On one hand, alterations in gut motility are linked to 5-HT dysmetabolism, in which the contents of 5-HT are higher in IBS-D. And the role of 5-HT has already been exploited as a therapeutic target with the use of 5-HT 3 , a subtype of 5-HT, receptor agonists [10].…”
Section: Discussionmentioning
confidence: 99%